The nature of love: Harlow, Bowlby and Bettelheim on affectionless mothers - van Rosmalen, Lenny; van der Veer, Rene; van der Horst, Frank C. P. (My University, 2020)
Harry Harlow, famous for his experiments with rhesus monkeys and cloth and wire mothers, was visited by psychiatrist and psychoanalyst John Bowlby and by child psychologist Bruno Bettelheim in 1958. They made similar observations of Harlow's monkeys, yet their interpretations were strikingly different. Bettelheim saw Harlow's wire mother as a perfect example of the 'refrigerator mother', causing autism in her child, while Bowlby saw Harlow's results as an explanation of how socio-emotional development was dependent on responsiveness of the mother to the child's biological needs. Bettelheim's solution was to remove the mother, while Bowlby specifically wanted to involve her in treatment. Harlow was very critical of Bettelheim, but evaluated Bowlby's work positively.
Keywords: attachment; autism; bettelheim; bowlby; harlow; mother love; refrigerator mother; wire mother